Unusual Fatigue Failure of a Cobalt-Chromium Alloy Cementless Femoral Stem: Implant Retrieval and Biomechanical Analysis - Nganbe, Michel; March, Gerard M.J.; Kim, Paul R.; Beaulé, Paul E. (CMBES Proceedings, 2013)
Recent premature failures of metal total hip replacements have raised concerns about their load bearing capacity, safety, reliability and survival rates. Specifically, femoral stem fracture is one of the most acute complications and results in greater morbidity and higher cost of revision hip surgery. In this contribution, we report an unusual case of fatigue failure of a cobalt-chromium alloy cementless femoral stem which functioned well for 24 years. Failure occurred at the neck-stem junction remote from any modular interface with only a minor traumatic event. Fractography, compositional and microstructural investigations revealed no intrinsic defect of the failed component. This late failure illustrates the importance of proper long-term testing of implants in regards to cyclic loading, as patients undergoing total joint replacement are increasingly younger and more active, putting implants at greater risk of long- term fatigue failure.